Locke's Twilight of Probability: An Epistemology of Rational Assent by Mark Boespflug - Trianni, Giorgio (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2025)
Review of Mark Boespflug's recent book, Locke's Twilight of Probability: An Epistemology of Rational Assent.(New York: Routledge, 2023)